Callus Induction of Curcuma longa L. and Effect of Precursor Addition on Curcuminoids Production - ศรีรัตน์, ปิยะมาศ; พราหมณีย์, รองศาสตราจารย์ ดร.สิริภัทร์; ศิริศันสนียกุล, รองศาสตราจารย์ ดร.สาโรจน์; ภระกูลสุขสถิตย์, ผู้ช่วยศาสตราจารย์ ดร.ประมุข; วาณิชย์ศรีรัตนา, รองศาสตราจารย์ ดร.วิรัตน์ (Journal of Food Health and Bioenvironmental Science, 2017)
This study aimed to investigate the callus induction and cultivation of Curcuma longa L. by using Rhizome bud as explants. The explants were cultivated on semi-solid B5 medium supplement with plant growth regulator auxin (1-naphthalene acetic acid (NAA) and 2,4-dichlorophenoxy acetic acid (2,4-D)) alone, or in combination with cytokinin (6-benzyladenine (BA) and N6-furfuryladenine (Kinetin)). The result showed that the addition of the appropriate plant growth regulators can induce calli. The HPLC analysis of the yellowish calli that were obtained from the medium supplement with 1 mg/L 2,4-D and 1 mg/L BA exhibited curcuminoids accumulation. The production of curcuminoids in calli can be improved by the supplementation of suitable precursors into the culture medium. The culture medium supplement with 5 μM phenylalanine and 5 μM malonic acid enhanced fresh weight of the calli and curcumioniods accumulation by 1.7 and 9.5 times higher than the control, respectively.